Response to selection for resistance to leaf feeding by fall armyworm in popG, a Guadeloupe maize population - Welcker, C.=700 1 Gilet, J.D.; Clavel, D.; Guinet, I.
Sumario (En)
Ilus.; 11 ref.
Keywords: ZEA MAYS; VARIACION GENETICA; SPODOPTERA FRUGIPERDA; RESISTENCIA A LAS PLAGAS; HEREDABILIDAD; INSTITUCIONES DE INVESTIGACION